2016
DOI: 10.1186/s12916-016-0553-2
|View full text |Cite|
|
Sign up to set email alerts
|

Post-marketing withdrawal of 462 medicinal products because of adverse drug reactions: a systematic review of the world literature

Abstract: BackgroundThere have been no studies of the patterns of post-marketing withdrawals of medicinal products to which adverse reactions have been attributed. We identified medicinal products that were withdrawn because of adverse drug reactions, examined the evidence to support such withdrawals, and explored the pattern of withdrawals across countries.MethodsWe searched PubMed, Google Scholar, the WHO’s database of drugs, the websites of drug regulatory authorities, and textbooks. We included medicinal products wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
364
0
20

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(387 citation statements)
references
References 35 publications
3
364
0
20
Order By: Relevance
“…5 Various Studies have shown that 462 medicinal products were withdrawn between 1953-2013 due to ADR reporting. 6 After the launch of the Pharmacovigilance Programme of India (PvPI) in 2010, Indian Pharmacovigilance has progressed tremendously, but a lot more has to be done to make the country truly pharmacovigilant. Under PvPI, Adverse drug reaction Monitoring Centre (AMC) set up in Medical colleges and Multispecialty Hospitals play a major role in collection and follow-up of ADR reports from healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…5 Various Studies have shown that 462 medicinal products were withdrawn between 1953-2013 due to ADR reporting. 6 After the launch of the Pharmacovigilance Programme of India (PvPI) in 2010, Indian Pharmacovigilance has progressed tremendously, but a lot more has to be done to make the country truly pharmacovigilant. Under PvPI, Adverse drug reaction Monitoring Centre (AMC) set up in Medical colleges and Multispecialty Hospitals play a major role in collection and follow-up of ADR reports from healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of such products from the market can result in loss of confidence in medications by the public and loss of effective compounds and loss of profit for drug manufacturers. 1 According to the US Food and Drug Administration (FDA), a drug is usually withdrawn from the market because of safety concerns that cannot be corrected or when its risks overshadow its benefits. Diacerein (DCN) is a drug used for the treatment of osteoarthritis (OA) at a dosage of 50-100 mg daily in two divided doses; it inhibits the synthesis and activity of interleukin 1-β (inflammatory mediator in OA).…”
Section: Introductionmentioning
confidence: 99%
“…Son yıllarda beklobrat, ketokonazol, nevirapin, nefazodon, sitaksentan sodyum vb etken maddeleri içeren ilaçlar dünyanın farklı bölgelerinde karaciğere bağlı yan etkiler nedeniyle piyasadan çekilmiştir [22].…”
Section: Hepatotoksisite çAlışmalarında Kök Hücrelerunclassified